1988
DOI: 10.1097/00000658-198807000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Metabolie Effects of Recombinant Human Growth Hormone in Patients Receiving Parenteral Nutrition

Abstract: Recombinant human methionyl growth hormone (Protropin) (Genetech, Inc., San Francisco, CA) administered to normal volunteers receiving hypocaloric parenteral nutrition minimized weight loss and induced positive nitrogen balance. To evaluate whether growth hormone (GH) can promote anabolism in surgical patients, 11 stable malnourished individuals were studied. In the initial trial, subjects received a constant parenteral infusion of a hypocaloric diet that provided approximately 1100 kcal/24 hr and 1.3 g protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(46 citation statements)
references
References 24 publications
2
43
0
1
Order By: Relevance
“…Many reports indicate that GH injections into adult ESRD patients decrease net urea production (urea nitrogen appearance) and/or serum urea, and sometimes serum phosphorus and potassium (10,12,14,23). These findings suggest more effective utilization of protein and amino acids.…”
Section: Effects Of Gh In Normal Individuals and People With Advancedmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports indicate that GH injections into adult ESRD patients decrease net urea production (urea nitrogen appearance) and/or serum urea, and sometimes serum phosphorus and potassium (10,12,14,23). These findings suggest more effective utilization of protein and amino acids.…”
Section: Effects Of Gh In Normal Individuals and People With Advancedmentioning
confidence: 99%
“…Serum albumin (11,18) or transferrin (14) rose in some trials. GH is reported to increase serum erythropoietin, leptin, IGF-I, and IGF binding protein-3, increase target organ sensitivity to parathyroid hormone and bone mineral density in GH-deficient people, and reduce serum parathyroid hormone levels (10,17,20,23,(35)(36)(37).…”
Section: Effects Of Gh In Normal Individuals and People With Advancedmentioning
confidence: 99%
“…2 Although specialized nutrition support improves the quality of patient care, it fails to ameliorate net protein catabolism. 3 Anabolic agents have been investigated for their use in preserving body cell mass and improving muscle strength. Studies in trauma and thermally injured patients reported improved nitrogen retention and restored muscle mass, but therapy was limited by androgenic complications.…”
Section: ! ! !mentioning
confidence: 99%
“…There are several studies that report improvement in the nitrogen balance ofseverely septic or injured patients following the administration of human growth hormone (26)(27)(28). As IGF-I may mediate the anabolic effects of growth hormone, IGF-I may possess some clinical potential in the nutritional support of such critically ill patients who typically have an accelerated rate ofprotein catabolism and who may have some degree of growth hormone resistance (29).…”
mentioning
confidence: 99%